Require Help With Simplification

csm

New member
Joined
Jan 22, 2014
Messages
4
How are these steps possible?




[(-1)^(2n+1)] . [(2n)^2] + [(-1)^(2n+2)] . [(2n+1)^2]


= [(-1) . (4n^2) + (4n^2 +4n + 1)


= 4n + 1
 
Last edited:
How are these steps possible?




[(-1)^(2n+1)] . [(2n)^2] + [(-1)^(2n+2)] . [(2n+1)^2]


= [(-1) . (4n^2) + (4n^2 +4n + 1)


= 4n + 1

correct...

Please use * for multiplication - at least on this board. It avoids confusion with decimal point.
 
How are these steps possible?




[(-1)^(2n+1)] . [(2n)^2] + [(-1)^(2n+2)] . [(2n+1)^2]


= [(-1) . (4n^2) + (4n^2 +4n + 1)


= 4n + 1
Assuming n is an integer, this is really a problem about odd and even powers of - 1. Odd powers = - 1, and even powers = + 1. Watch below how it works using the laws of exponents.

\(\displaystyle (- 1)^{(2n + 1)} = (-1)^{(2n)} * (-1)^1 = \left(\{(-1)^2\}^n\right) * (-1)^1 = (1)^n * (- 1) = 1 * (- 1) = - 1.\) You OK with that?

\(\displaystyle (- 1)^{(2n + 2)} = \left\{(-1)^2\right\}^{(n + 1)} = 1^{(n + 1)} = 1.\) Is that clear?

\(\displaystyle So\ \left\{(-1)^{2n + 1)} * (2n)^2\right\} + \left\{(-1)^{(2n + 2)} * (2n + 1)^2\right\} =\)

\(\displaystyle \left\{(-1) * (2n)^2\right\} + \left\{1 * (2n + 1)^2\right\} =\)

\(\displaystyle \left\{(-1) * 4n^2\right\} + \left\{1 * (4n^2 + 4n + 1)\right\} =\)

\(\displaystyle - 4n^2 + 4n^2 + 4n + 1 =\)

\(\displaystyle 4n + 1\)

Clear now?
 
Top